Faktor-Faktor yang Berhubungan dengan Kesehatan Reproduksi Remaja Putri di SMA Negeri 1 Ulu Moro’o Nias Barat Tahun 2021 - Lindawati Simorangkir; Jagentar Pane; Eva Damayanthi Gulo (Journal of Indah Science and Clinic, 2022)
Reproductive health is a significant issue that should be a worry, particularly among teenagers. Regenerative wellbeing is finished physical, mental and social wellbeing, not restricted to sickness or connected with conceptive frameworks, works and cycles as well as mental, social and social wellbeing. This study was to describe the factors related to the reproductive health of adolescent girls at SMAN 1 Ulul Moro'o in 2021. This type of research used a descriptive research design. The population of young women in SMAN 1 Ulu Moro'o West Nias with a sample of 48 people. The inspecting strategy utilized was total sampling. The estimating instrument utilized is a questionnaire. The results on the information and perspectives of young ladies about reproductive health at SMAN 1 Ulul Moro'o West Nias in 2021 were found in a very good category, namely 34 respondents (70.8%). SMAN 1 Ulu Moro'o, West Nias in 2021 in the great class, upwards of 29 respondents (60.4%). It is trusted that the after effects of this review will empower the school to give help with planning young ladies to work on their reproductive health.